PRINCIPALS AS MANAGERS IN IMPROVING LEARNING QUALITY IN 3T SCHOOLS: A TANIMBAR SELATAN MULTI-SITE STUDY - Friska Fordatkosu; Patrisius Rahabav; Paulus Liberthy Wairisal (SOSIOEDUKASI, 2026)
Principal managerial leadership is a decisive factor in improving learning quality, particularly in Indonesia's disadvantaged, frontier, and outermost (3T) areas, where schools face limited facilities, teacher shortages, unstable internet access, and complex community conditions. This study aims to analyze the role of principals as managers in planning, organizing, actuating, and controlling learning at SMP Santo Paulus Saumlaki and SMP Negeri 2 Tanimbar Selatan. A qualitative multi-site design was applied. Data were collected through semi-structured interviews with principals, teachers, school staff, and committee representatives; direct observation of school activities; and documentation of school programs, supervision records, learning schedules, and planning documents. Data were analyzed using reduction, display, conclusion drawing, and cross-site comparison. Credibility was strengthened through source triangulation, method triangulation, and member checking. The findings show that the principal of SMP Santo Paulus applied an adaptive-collegial managerial pattern supported by teacher solidarity, flexible planning, and humanistic supervision. Meanwhile, the principal of SMP Negeri 2 Tanimbar Selatan applied a transformational-structured pattern supported by formal programs, standardized supervision, and broader community networks. Both models improved learning management, although they faced different constraints. SMP Santo Paulus struggled with limited documentation, facilities, and standardized supervision, while SMP Negeri 2 faced bureaucratic constraints, teacher participation polarization, and student literacy problems. This study contributes to educational management by showing that principal managerial effectiveness in 3T schools depends on contextual adaptation, not a single universal leadership model.